Changes in percentages of perceived met needs for care over time in a Canadian longitudinal cohort. (November 2018) - Meng, Xiangfei; Fleury, Marie-Josee; Bamvita, Jean-Marie; Grenier, Guy; Caron, Jean
Highlights: This study firstly explored changes in percentages of perceived met needs and their associated determinants. Percentages of perceived met needs slightly increased overtime. Mental well-being and change in wellbeing were positively associated with changes in percentages of perceived met needs. Percentages of perceived met needs at baseline were negatively linked with changes in percentages of perceived met needs. Mental well-being could be the target for improving perceived need of mental health care. Abstract: There is a paucity of research on determinants associated with changes in perceived met needs for care over time. This study used a longitudinal cohort to explore changes in percentages of perceived met needs over time and to identify its related determinants. Data analyzed was from a longitudinal community-based survey. A total of 150 participants received at least one type of help both at baseline and a 2-year follow-up. Multivariate analyses were used. Perceived met needs of the study sample slightly increased over time. People who had a higher percentage of met needs at baseline were less likely to have an increase in percentage of perceived met needs at the 2-year follow-up, whereas, those who had a higher value of wellbeing and an increase in the value of mental wellbeing over time, were associated with an increase in the percentage of met needs at the 2-year follow-up. Determinants associated with changes in percentages of perceived met needs could be the target for improving perceived need for mental health care. Findings of this study indicate the need for longitudinal studies in perceived need for mental health services.